2023
DOI: 10.2147/prbm.s401082
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multi-Quality Renewal Elements of Residence on the Subjective Well-Being of the Older Adults - A Case Study of Dalian

Abstract: Background: With the expansion of comprehensive renovation projects in China's old residential areas, residents' actual sense of access and well-being has become a source of concern. As the population in old residential areas ages, the results of old renovation will have a significant impact on the older adults quality of life and subjective well-being. Purpose: To date, most relevant studies have focused on urban and community scales, with little discussion of the impact of neighborhood-level renewal outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Research has found that urban renewal brings about changes in social capital, which is positively correlated with changes in residential satisfaction ( 46 ). In addition, some scholars have focused their research on older adults and found that their living satisfaction is positively affected by the living environment during urban renewal ( 48 ). The different modes of urban renewal can also affect residential satisfaction, and affect satisfaction through factors such as residential conditions, neighborhood relationships, and economic expectations ( 49 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that urban renewal brings about changes in social capital, which is positively correlated with changes in residential satisfaction ( 46 ). In addition, some scholars have focused their research on older adults and found that their living satisfaction is positively affected by the living environment during urban renewal ( 48 ). The different modes of urban renewal can also affect residential satisfaction, and affect satisfaction through factors such as residential conditions, neighborhood relationships, and economic expectations ( 49 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Part of the research focuses on urban renewal and residential satisfaction. It is clearly proposed that urban development and renewal will affect residents' housing satisfaction (45)(46)(47)(48). Research has found that urban renewal brings about changes in social capital, which is positively correlated with changes in residential satisfaction (46).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A decline in subjective well-being can potentially trigger adverse psychological and physical health outcomes 3,6 . Therefore, understanding the foundations of subjective well-being and its in uencing factors is vital for enhancing individual happiness levels 7 . Despite advancements in subjective well-being research, there needs to be more studies explicitly focused on the college student population in Yunnan Province, China.…”
Section: Introductionmentioning
confidence: 99%